Electrospraying and Electrospinning of Chocolate Suspensions - Luo, C; Loh, S; Stride, E; Edirisinghe, M (2012)
Novel applications of efficient and economical techniques such as electrospraying and electrospinning in chocolate processing could be a strategy to help manufacturers improve declining sales growth rate in a saturated confectionery market. In this study, electrosprayed near-monodisperse particles have been produced using chocolate suspensions. Electrospun fibres have also been created from a commercial chocolate sauce. The effects of process parameters such as sugar concentration, addition of electrolytes (NaCl), flow rate, applied voltage and collection distance on the production and morphology of as-sprayed chocolate particles were studied. A positive linear trend in the electrosprayed chocolate particle diameter and diameter distribution range with increasing sugar concentration in the chocolate suspension was demonstrated. Sugar concentrations of 30-35%w/w resulted in very fine, near-monodisperse chocolate particles. Trace amounts of electrolyte at 1%w/w were found to decrease the average particle diameter and improve the monodispersity of the particles produced. The addition of NaCl at low concentrations increased the electrical conductivity and, to a lesser extent, the surface tension of the chocolate samples. Further increases in NaCl concentration to 3%w/w did not bring any additional decrease in the average diameter of the chocolate particles. In addition, the observed modes of electrospraying and the characteristics of chocolate particles obtained under these were investigated. Bead-on-string morphology was commonly observed among electrospun chocolate fibres. Moreover, satellite particles and very fine fibres were obtained during the transition between electrospraying and electrospinning. The continuous alternating shape of elongated spheres and thin fibres may have the potential for varying the microtexture of the chocolate products. © 2011 Springer Science + Business Media, LLC.